THE EFFECT OF NATURAL GUARD IN DRINKING WATER ON NEWCASTLE DISEASE ANTIBODY TITER IN LAYING HENS - Maulidiyah, Misfah; Ardana, Ida Bagus Komang; Suardana, Ida Bagus Kade (Buletin Veteriner Udayana, 2025)
Natural Guard is a combination of pine oil, lavender oil and eucalyptus oil which can be used as an immunomodulator. The aim of this study was to determine the effect of Natural Guard administration through drinking water on the antibody titer against Newcastle Disease (ND) virus. This study used 24 Hy-line Brown laying hens randomly assigned to four treatment groups. Natural Guard was mixed into the drinking water at different concentrations: 0 ml/L (control), 0.1 ml/L (P1), 0.2 ml/L (P2), and 0.3 ml/L (P3), and administered for 30 days. ND antibody titers were measured using the Hemagglutination Inhibition (HI) test. The data obtained were analyzed using analysis of variance. The results showed that administration of Natural Guard at doses of 0.1 ml/L, 0.2 ml/L, and 0.3 ml/L did not significantly (P > 0.05) increase ND virus antibody titers in laying hens.